Electrode assembly and secondary battery including same

By adjusting the wet adhesion of the separation membrane to the negative electrode, the bending problem caused by large-capacity batteries is solved due to the large expansion rate of the negative electrode, and the stability and efficient assembly of the battery module are achieved.

JP2025511607AActive Publication Date: 2025-04-16LG ENERGY SOLUTION LTD

Patent Information

Application Number
JP2024556628
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-12-14
Filing Date
2023-12-15
Publication Date
2025-04-16
Estimated Expiration
2043-12-15

AI Technical Summary

Technical Problem

The negative electrode of a large-capacity battery contains silicon-based active substances and has a large expansion rate, which causes the adhesion force to change with the positive electrode and the separation membrane, causing the battery module to bend or deform, affecting the shape and performance of the battery.

Method used

By adjusting the wet adhesion of the separation membrane to the negative electrode to make it between 1.5 gf/20 mm and 15 gf/20 mm, ensuring that bending is avoided after the battery activation step.

Benefits of technology

It effectively prevents the bending and deformation of the battery module, improves the assembly efficiency and energy density of the battery, and maintains the stability of the battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025511607000001_ABST
    Figure 2025511607000001_ABST
Patent Text Reader

Abstract

An electrode assembly and a secondary battery including the same are provided, the electrode assembly including a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode, the wet adhesive strength of the separator to the negative electrode being 1.5 gf / 20 mm or more and 15 gf / 20 mm or less. When the wet adhesive strength of the separator of the electrode assembly to the negative electrode satisfies the above range, distortion of the electrode assembly is effectively prevented before impregnation with an electrolyte, and bending phenomenon after activation of the electrode assembly and the secondary battery including the same can be more effectively suppressed after impregnation with an electrolyte.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] [CROSS REFERENCE TO RELATED APPLICATIONS] This application claims the benefit of the filing date of Korean Patent Applications Nos. 10-2022-0177177, 10-2022-0177190, and 10-2022-0177156, filed on December 16, 2022, and all contents disclosed in the documents of those Korean patent applications are incorporated herein by reference.

[0002] The present invention relates to an electrode assembly and a secondary battery including the same. [Background technology]

[0003] Secondary batteries are divided into coin batteries, cylindrical batteries, square batteries, pouch batteries, etc. depending on the shape of the battery case. Unlike primary batteries, secondary batteries can be recharged, and there is growing potential for them to be made smaller and have larger capacities, so much research and development has been done on them in recent years.

[0004] Recently, as electric vehicles (EVs) have become more popular, there has been an increase in technological development and demand for large-capacity secondary batteries for use in EVs. In order to manufacture large-capacity secondary batteries, the size of an electrode assembly mounted inside a battery case is also increasing. When the size of the electrode assembly is large, problems that were not anticipated in the case of a small-sized electrode assembly may occur.

[0005] The electrode assembly is a power generating element that can be charged and discharged, and is made up of a laminated structure of electrodes and separators. The separators include an organic / inorganic composite porous coating layer, and provide adhesion between the electrodes and the separator. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Korean Patent Publication No. 10-2013-0132230 Summary of the Invention [Problem to be solved by the invention]

[0007] The electrode assembly is mounted inside a battery case and then goes through a packaging process and / or an activation process to manufacture a secondary battery. However, when the negative electrode contains a silicon-based active material, the expansion rate of the negative electrode is greater than that of the positive electrode before and after the activation process, which causes a bending phenomenon in which the electrode assembly is warped or bent due to variations in the adhesive strength between the separator and the electrode, resulting in a problem of deformation of the shape of the secondary battery itself.

[0008] In particular, when the size of an electrode assembly is large, such as a large-capacity electrode assembly, the difference between the expansion rates of the negative electrode and the positive electrode becomes more significant, and the bending phenomenon may become a major problem. Therefore, there is a need to develop technology to prevent the bending phenomenon in a large-capacity electrode assembly or a secondary battery including the same. [Means for solving the problem]

[0009] One embodiment of the present invention provides an electrode assembly including a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode, wherein the wet adhesive strength of the separator to the negative electrode is 1.5 gf / 20 mm or more and 15 gf / 20 mm or less.

[0010] One embodiment of the present invention provides a secondary battery comprising a sealed battery case, an electrode assembly according to the embodiment contained inside the battery case, and an electrolyte contained inside the battery case, and satisfying the following formula 1:

[0011] [Formula 1] X<5mm In the above formula 1, X means the maximum distance measured from an imaginary reference line connecting two opposing sides of the upper surface of the secondary battery to the lowest point of the upper surface of the secondary battery in a state where the secondary battery is placed on a flat surface with the concave side of the secondary battery facing up after the activation process of the secondary battery. Effect of the Invention

[0012] The electrode assembly according to the embodiment of the present invention has an effect of preventing bending that may occur after activation of a secondary battery including the electrode assembly, particularly in a large-sized electrode assembly.

[0013] The electrode assembly according to the embodiment of the present invention can prevent bending phenomenon, thereby preventing process defects after activation of the battery and improving assembly yield. In addition, the electrode can be fixed without shifting in position, which leads to improved energy density.

[0014] A secondary battery including an electrode assembly according to an embodiment of the present invention can prevent bending, thereby improving assembly yield after activation and maintaining good alignment of the electrodes, which also leads to prevention of deterioration of cell performance. [Brief description of the drawings]

[0015] [Figure 1] 1 is a schematic cross-sectional view of a separator according to one specific embodiment of the present invention. [Diagram 2] 1 shows an image of the surface of a separator according to a specific embodiment of the present invention. [Diagram 3] 13A and 13B are diagrams showing that problems due to bending phenomenon can be exacerbated in the case of a large-area electrode assembly. [Figure 4] 4A to 4C are diagrams showing one method for measuring bending of an electrode assembly according to the present application. [Diagram 5] FIG. 2 is a schematic diagram of a separator according to the present invention. [Figure 6]4A to 4C are cross-sectional views showing a process flow of an electrode assembly manufacturing apparatus according to an embodiment of the present invention. [Figure 7] 1 is a plan view showing a process flow of an electrode assembly manufacturing apparatus according to an embodiment of the present invention; [Figure 8] 1 is a cross-sectional view illustrating an example of an electrode assembly manufactured by an electrode assembly manufacturing apparatus and an electrode assembly manufacturing method according to an embodiment of the present invention; [Figure 9] 1A is a perspective view showing a first heat press unit 50, and FIG. 1B is a perspective view showing a second heat press unit 60. FIG. [Figure 10] 4 is an image taken to check whether or not there are wrinkles in the separator of the electrode assembly according to Example 1. [Figure 11] 13 is an image taken to check whether or not there are wrinkles in the separator of the electrode assembly according to Comparative Example 14. [Figure 12] 1 is an image taken to confirm the meandering nature of the electrode assembly according to Example 1. [Figure 13] 13 is an image taken to confirm the meandering nature of the electrode assembly according to Comparative Example 11. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The present invention may, however, be embodied in many different forms and should not be construed as limited to the embodiments set forth herein.

[0017] In this specification, when a part is said to "comprise" a certain component, this means that it may further include other components, rather than excluding other components, unless specifically stated to the contrary.

[0018] In this specification, the "area" of an electrode assembly refers to the area of ​​a surface that can be seen when the electrode assembly is viewed from above in the stacking direction in which the electrodes and separators contained in the electrode assembly are stacked, i.e., the area of ​​the electrode assembly surface perpendicular to the stacking axis.

[0019] In the present specification, the term "dry adhesive strength" refers to the adhesive strength of a separator measured when an electrode assembly including a separator is not immersed in an electrolyte solution. That is, it refers to the adhesive strength of a separator measured before an activation step of the electrode assembly. In the present specification, the dry adhesive strength is also referred to as the adhesive strength of a separator in a dry state.

[0020] In the present specification, the term "wet adhesive strength" refers to the adhesive strength of a separator measured when an electrode assembly including the separator is immersed in an electrolyte. That is, it may refer to the adhesive strength of a separator measured after activation of the electrode assembly or after charging and discharging the battery. In the present specification, the wet adhesive strength may also be referred to as the adhesive strength of a separator when immersed in an electrolyte.

[0021] In this specification, the dry adhesive strength and the wet adhesive strength can be measured by cutting the electrode assembly into a size of 20 mm x 70 mm to prepare a test piece in which a positive electrode, a separator, and a negative electrode are stacked, and then peeling the separator of the test piece at a speed of 100 mm / min using a tensile tester (UTM equipment) in a 90° peeling mode from one side of the separator. In this case, the measurement is performed in the longitudinal direction of the test piece (parallel to the 70 mm side). That is, except for whether the electrode assembly is impregnated with an electrolyte, the methods for measuring the dry adhesive strength and the wet adhesive strength are the same. In addition, the absolute value of the difference between the measured adhesive strengths can be defined as the deviation of the adhesive strength.

[0022] In this specification, the term "activation" or "activation process" of a secondary battery refers to a process (or step) of activating the secondary battery through a charging process and removing gas.

[0023] <Electrode assembly> An embodiment of the present invention provides an electrode assembly in which the separator has a certain degree of wet adhesion to the negative electrode. That is, the electrode assembly according to the present invention means that the separator has a certain degree of adhesion to the negative electrode even after being immersed in an electrolyte. The adhesion between the separator and the negative electrode may be affected by the type and physical properties of the separator, the material of the coating layer on the surface of the separator, the lamination conditions of the electrode assembly, the activation conditions, the material of the negative electrode, and the like. For example, the wet or dry adhesion to the negative electrode may differ depending on the type, physical properties, or material of the separator. In addition, the wet or dry adhesion between the separator and the negative electrode may change depending on the conditions applied in the process of laminating the positive electrode, the negative electrode, and the separator of the electrode assembly, and / or the activation conditions of the secondary battery. In addition, the degree of expansion or bending of the negative electrode during charging and discharging of the secondary battery may change depending on the material of the negative electrode, which may affect the wet or dry adhesion between the separator and the negative electrode.

[0024] In one embodiment of the present invention, the wet adhesive strength of the separator to the negative electrode is 1.5 gf / 20 mm or more and 15 gf / 20 mm or less. According to one example, the wet adhesive strength of the separator to the negative electrode may be 2 gf / 20 mm or more, 2.5 gf / 20 mm or more, 3 gf / 20 mm or more, 3.5 gf / 20 mm or more, or 4 gf / 20 mm or more. The wet adhesive strength of the separator to the negative electrode may be 15 gf / 20 mm or less, 12 gf / 20 mm or less, 10 gf / 20 mm or less, 8 gf / 20 mm or less, 7 gf / 20 mm or less, 6 gf / 20 mm or less, or 5 gf / 20 mm or less.

[0025] When the wet adhesive strength satisfies the above range, the wet adhesive strength of the separator to the negative electrode is at least a certain value, and therefore the separator can be fixed to the negative electrode, and since the wet adhesive strength is not excessive, bending of the electrode assembly during an activation process of a secondary battery including the electrode assembly can be easily prevented, thereby improving the performance of the secondary battery.

[0026] In one embodiment of the present invention, the dry adhesive strength of the separator to the negative electrode may be 8 gf / 20 mm or more, 10 gf / 20 mm or more, 12 gf / 20 mm or more, 14 gf / 20 mm or more, or 15 gf / 20 mm or more. In addition, the dry adhesive strength of the separator to the negative electrode may be 25 gf / 20 mm or less, 23 gf / 20 mm or less, 20 gf / 20 mm or less, or 18 gf / 20 mm or less. When the dry adhesive strength satisfies the above range, the electrode assembly manufactured in the stacking process can be more easily transported while maintaining the laminated structure. That is, it is possible to prevent the performance of the electrode assembly from being degraded due to the position of the electrodes being shifted during the transportation process, and as a result, the performance of the manufactured electrode assembly is also more excellent. In addition, since the dry adhesive strength does not have an excessively high dry adhesive strength, it is advantageous to have an appropriate level of wet adhesive strength after impregnation with an electrolyte.

[0027] According to one example, the wet adhesive strength may be 40% or less, 35% or less, or 33% or less of the dry adhesive strength. According to another example, the wet adhesive strength may be 10% or more, 15% or more, 20% or more, or 25% or more of the dry adhesive strength. When the wet adhesive strength of the separator of the electrode assembly to the negative electrode satisfies the above range, the electrode assembly can be effectively prevented from shifting before impregnating with the electrolyte, and after impregnating with the electrolyte, the electrode assembly and the secondary battery including the same can be more effectively prevented from bending after activation. Specifically, the dry adhesive strength is required to maintain the laminated structure of the electrode assembly in the stacking process, and the wet adhesive strength is within the above range. If the wet adhesive strength is too strong, the bending may be further accelerated due to the difference in the expansion coefficient between the negative electrode and the positive electrode.

[0028] According to one embodiment, the negative electrode includes a silicon-based active material. In this case, the negative electrode has a higher expansion rate after activation than a positive electrode that does not include a silicon-based active material. In this case, if the adhesive strength does not satisfy the above range, the expansion of the negative electrode and the difference in the expansion rates of the negative electrode and the positive electrode cause unevenness in the adhesive strength between the separator and the electrode, resulting in a bending phenomenon in which the electrode assembly is warped or bent.

[0029] However, in the electrode assembly according to the present invention, since the separator of the electrode assembly has a certain degree of dry adhesive force and wet adhesive force to the negative electrode, it is possible to prevent the laminated structure of the electrodes and separator included in the electrode assembly from being distorted during the manufacturing process of the electrode assembly, while minimizing the occurrence of uneven adhesive force between the electrodes and the separator due to expansion of the negative electrode and the difference in expansion rate between the negative electrode and the positive electrode. That is, it is possible to simultaneously prevent the laminated structure of the electrodes and the separator from being distorted during the stacking process and the bending phenomenon after bending activation.

[0030] In one embodiment of the present invention, the separator may contain 0.1 parts by weight or more, 2 parts by weight or more, 3 parts by weight or more, or 4 parts by weight or more of fluorine (F) relative to 100 parts by weight of the separator surface component. The separator may contain 8 parts by weight or less, 6 parts by weight or less, or 5 parts by weight or less of fluorine (F) relative to 100 parts by weight of the separator surface component.

[0031] In the present specification, the surface of the separator may be observed by photographing the surface of the separator using a scanning electron microscope (SEM). The term "separator surface components" refers to components measured at a portion (hereinafter, separator surface) of the separator, which is formed with an organic / inorganic composite porous coating layer, photographed at an accelerating voltage of 15.0 kV and a magnification of 10,000 times using a scanning electron microscope (SEM), as shown in FIG. 2, after disassembling the secondary battery after activating the secondary battery to obtain a separator, immersing the separator in a dimethyl carbonate solvent for 30 minutes to remove electrolyte additives and metal salt components remaining on the surface, and then drying the separator at room temperature for 24 hours.

[0032] More specifically, the components measured by analyzing the separator surface using energy dispersive X-ray spectroscopy (EDS) are defined as the separator surface components, and the sum of the components measured by the energy dispersive X-ray spectroscopy (EDS), i.e., the total elements contained in the part visible in the SEM image, can be defined as 100 parts by weight. In this case, the surface component analysis using energy dispersive X-ray spectroscopy (EDS) can be carried out while taking an image at 15 kV and 10,000 times magnification.

[0033] That is, the content of fluorine (F) is 0.1 to 8 parts by weight based on 100 parts by weight of the separator surface component means that the relative content of fluorine based on the 100 corresponds to 0.1 to 8.

[0034] The separator containing fluorine (F) in the above range per 100 parts by weight of the separator surface component means that the separator contains a fluorine-based binder even before it is immersed in an electrolyte. Due to the presence of the fluorine-based binder, the separator can have adhesive strength (dry adhesive strength) to the electrode even before the electrode assembly according to the present invention is immersed in an electrolyte. In addition, the separator surface containing fluorine in the above amount means that the above range of dry adhesive strength of the electrode assembly can be satisfied.

[0035] In one embodiment of the present invention, the separator may be folded and stacked in a zigzag shape, that is, the electrode assembly according to one embodiment of the present invention may be zigzag stacked.

[0036] In this specification, stacking the positive and negative electrodes alternately between the folded separators is referred to as zigzag stacking.

[0037] In this case, the folded separator may refer to a separator in which the separators are stacked in a zigzag manner. More specifically, the separators are stacked in a zigzag manner while being folded in a manner that alternates between the left side and the right side of the stacking axis based on the stacking axis. The stacked separators are stacked in a manner that the positive and negative electrodes are alternately arranged between the stacked separators. Here, the stacking axis is a virtual axis that is parallel to the direction in which the positive electrode, the separator, and the negative electrode are stacked, and passes through the center of the stacked body in which the electrodes and the separators are stacked.

[0038] In other words, the positive electrodes and the negative electrodes are alternately arranged between the separators means that the separators are stacked in a zigzag pattern in the direction of the stacking axis, and the positive electrodes and the negative electrodes are alternately inserted one by one into the spaces (between the separators) generated as the separators overlap.

[0039] To perform the zig zag stacking, techniques or devices commonly used in the art can be used.

[0040] In an embodiment of the present invention, the electrode assembly may have a rated capacity of 50 Ah to 200 Ah, preferably 50 Ah to 150 Ah, and more preferably 60 Ah to 140 Ah.

[0041] In one embodiment of the present invention, the wet adhesion strength of the separator to the negative electrode may be greater than the wet adhesion strength of the separator to the positive electrode.

[0042] In one embodiment of the present invention, the wet adhesive strength of the separator to the negative electrode may be 1 or more, 1.1 or more, or 1.2 or more times the wet adhesive strength of the separator to the positive electrode. The wet adhesive strength of the separator to the negative electrode may be less than 1.5 or 1.4 times the wet adhesive strength of the separator to the positive electrode.

[0043] According to one example, the difference between the magnitude of the wet adhesive strength of the separator to the negative electrode and the magnitude of the wet adhesive strength of the separator to the positive electrode may be 5 gf / 20 mm or less, 3 gf / 20 mm or less, 1.5 gf / 20 mm or less, or 1.2 gf / 20 mm or less, the difference being the absolute value of the difference in the magnitude of the adhesive strength.

[0044] As described above, the wet adhesive strength is measured in a state where the electrode assembly is immersed in an electrolyte solution, and it is preferable that the difference in the wet adhesive strength is small in terms of preventing the bending effect from occurring.

[0045] In one embodiment of the present invention, the dry adhesion of the separator to the negative electrode may be greater than the dry adhesion of the separator to the positive electrode.

[0046] In one example, the dry adhesive strength of the separator to the negative electrode may be 1 or more times, or 1.1 or more times, the dry adhesive strength of the separator to the positive electrode, and the dry adhesive strength of the separator to the negative electrode may be 2.5 or less times, 2 or less times, 1.5 or less times, or 1.3 or less times, the dry adhesive strength of the separator to the positive electrode.

[0047] In one embodiment of the present invention, the difference between the magnitude of the dry adhesive strength of the separator to the negative electrode and the magnitude of the dry adhesive strength of the separator to the positive electrode may be 10 gf / 20 mm or less, 8 gf / 20 mm or less, 7 gf / 20 mm or less, 5 gf / 20 mm or less, 4 gf / 20 mm or less, or 3 gf / 20 mm or less, where the difference means the absolute value of the difference in the magnitude of the adhesive strength.

[0048] The smaller the difference in dry adhesive strength is, the less the difference in wet adhesive strength can be controlled in the processes following the stacking process.

[0049] In one embodiment of the present invention, the upper surface of the electrode assembly may be rectangular having short and long sides, and the ratio of the length of the long side to the length of the short side may be 3 to 12. The rectangular shape refers to the electrode assembly as viewed in the stacking direction.

[0050] In one embodiment of the present invention, the area of ​​the electrode assembly is 500 cm 2 It may be more than that.

[0051] In one embodiment of the present invention, the electrode assembly may have a total length of 400 mm or more and a total width of 50 mm or more.

[0052] More specifically, in one embodiment of the present invention, one surface of the electrode assembly may be rectangular having short and long sides, with a total length of 400 mm to 600 mm and a total width of 50 mm to 150 mm.

[0053] An electrode assembly having the above size may be defined herein as a large area electrode assembly.

[0054] In one embodiment of the present invention, the overall length of the electrode assembly refers to the length of a longer side of the electrode assembly, and refers to the length in a direction perpendicular to the supply direction of the separator supplied during the manufacture of the electrode assembly.

[0055] In the case of an electrode assembly having a large number of stacked electrodes and a total length of 400 mm or more, the difference in the expansion rates of the negative and positive electrodes has a greater impact, which can lead to greater problems due to bending (warping or warping) of the electrode assembly.

[0056] As shown in Fig. 3, even if the angle c is the same, the greater the distance from the reference point, the greater the distance from the horizontal. That is, if a small electrode assembly is bent or warped by angle c, and the distance from the horizontal to the end of the electrode assembly is a, then in the case of a large electrode assembly, the distance from the horizontal to the end of the electrode assembly under the same conditions will be b. That is, it can be seen that the distance from the horizontal to the end of the electrode assembly is greater for the large electrode assembly, which means that problems due to bending may occur to a greater extent in the case of a large electrode assembly.

[0057] That is, even if the electrode assembly is warped or sagged at the same angle, the bending phenomenon may be a relatively greater problem when the electrode assembly is large than when the electrode assembly is small.

[0058] Also, even if the electrode assembly is heated and pressed to be manufactured flat, due to the large number of stacked electrodes, there is a problem of shrinkage and expansion, and there are limitations. However, in the case of the present invention, by satisfying the conditions such as the adhesive force of the separator described above, bending of the secondary battery can be prevented after the activation process.

[0059] In one embodiment of the present invention, the negative electrode contains a silicon-based active material. The silicon-based active material may contain at least one of a silicon-carbon composite and a silicon oxide. For example, the silicon-based active material may contain a silicon-carbon composite, a silicon oxide, or both. The silicon-based oxide is a material containing SiOx (0 < x < 2). The negative electrode may further contain a carbon-based active material. Graphite can be used as the carbon-based active material. For example, the negative electrode may contain 1 to 40 parts by weight, 2 to 30 parts by weight, 3 to 15 parts by weight, or 4 to 10 parts by weight of the silicon-based active material per 100 parts by weight of the active material.

[0060] In one embodiment of the present invention, the negative electrode includes a negative electrode current collector; and a negative electrode active material layer located on at least one surface of the negative electrode current collector and containing a negative electrode active material, a binder, and a conductive material. The negative electrode active material layer includes a lower layer region in surface contact with the negative electrode current collector and an upper layer region extending to the surface of the negative electrode active material while being in surface contact with the lower layer region. At least one of the lower layer region and the upper layer region may contain a silicon-based active material. Optionally, both the lower layer region and the upper layer region may contain a silicon-based active material. At least one of the lower layer region and the upper layer region may further contain a carbon-based active material.

[0061] Here, "surface contact" means a form in which surfaces are in contact.

[0062] In one embodiment of the present invention, the separator may include a porous substrate and an organic / inorganic composite porous coating layer formed on at least one surface of the porous substrate. In the electrode assembly according to the present invention, since the separator must have adhesive strength to the negative electrode, the one surface of the separator may be in contact with the negative electrode.

[0063] In one embodiment of the present invention, the separator may include a porous substrate and an organic / inorganic composite porous coating layer provided on at least one of one and the other surfaces of the porous substrate. That is, one of the two surfaces of the separator is a surface that contacts the negative electrode, and the other surface of the separator is a surface that contacts the positive electrode, and when the organic / inorganic composite porous coating layer is formed on both surfaces of the separator, the separator may have adhesive strength to the negative electrode and the positive electrode, respectively.

[0064] In one embodiment of the present invention, the organic / inorganic composite porous coating layer may contain one or more types of particulate binder resins and one or more types of inorganic particles.

[0065] Specifically, Fig. 1 is a schematic cross-sectional view of a separator according to a specific embodiment of the present invention, and the separator 14 includes a porous substrate 1 and an organic / inorganic composite porous coating layer 2 formed on at least one surface of the porous substrate. Although Fig. 1 shows that the organic / inorganic composite porous coating layer 2 is formed on only one surface of the porous substrate 1, the organic / inorganic composite porous coating layer 2 of the separator of the present invention may also be formed on the other surface of the porous substrate 1. The organic / inorganic composite porous coating layer 2 includes particulate binder resins 4, 5 and inorganic particles 3. As will be described later, the particulate binder polymers 4, 5 may be a fluorine-based polymer 4 and an acrylic polymer 5, respectively.

[0066] In one embodiment of the present invention, the particulate binder resin may include an acrylic polymer and a fluorine-based polymer.

[0067] According to one example, the weight ratio of the acrylic polymer and the fluoropolymer may be 20:80 to 60:40. The fluoropolymer may affect wet adhesion. The surface of the separator serves as an adhesive layer with the electrode, but if the acrylic polymer is present in excess on the surface of the separator, it may cause a decrease in wet adhesion. For example, when the particle size of the acrylic polymer is 350 nm to 450 nm and the density is 1.4 to 1.6, and the particle size of the fluoropolymer is 250 nm to 400 nm and the density is 1.6 to 1.8, it is favorable for the acrylic polymer to move to the surface of the separator in the migration of the surface part due to the difference between the emulsion particle size and density. Therefore, it is preferable to adjust the content of the acrylic polymer to 60 parts by weight or less as described above. Also, when the amount of the acrylic polymer is less than 20 parts by weight, the dry adhesion decreases, and the adhesion between the positive electrode and the separator is maintained strong, while the adhesion between the negative electrode and the separator is relatively decreased, and defects due to bending may occur.

[0068] In one embodiment of the present invention, the fluoropolymer may be a homopolymer of vinylidene fluoride (PVDF), a copolymer of vinylidene fluoride and another polymerizable monomer, or a mixture of two or more thereof.

[0069] More specifically, the vinylidene fluoride and other polymerizable monomers may be at least one selected from the group consisting of tetrafluoroethylene, hexafluoropropylene, trifluoroethylene, chlorofluoroethylene, 1,2 difluoroethylene, perfluoro(methyl vinyl) ether, perfluoro(ethyl vinyl) ether, perfluoro(propyl vinyl) ether, perfluoro(1,3 dioxole), perfluoro(2,2-dimethyl-1,3-dioxole), trichloroethylene, and vinyl fluoride, but are not limited thereto. In particular, the fluorine-based polymer may be a copolymer (PVdF-HFP) of vinylidene fluoride and hexafluoropropylene (HFP). The content of vinylidene fluoride and other polymerizable monomers may be 1% by weight to 20% by weight, preferably 3% by weight to 18% by weight, of the copolymer. The other polymerizable monomer is for increasing wet adhesion, and if the content is less than 1 wt%, wet adhesion may be difficult to generate, and if the content exceeds the above content, the resistance of the separator may be too high, which may deteriorate the performance of the electrode assembly. For example, the fluorine-based polymer may be a copolymer (PVdF-HFP) of vinylidene fluoride and hexafluoropropylene (HFP), and the hexafluoropropylene may be 3 to 18 parts by weight based on 100 parts by weight of the comonomer constituting the copolymer (PVdF-HFP). When the content of HFP is 3 parts by weight or more, it is possible to obtain a certain level of wet adhesion, and when the content is 18 parts by weight or less, it is possible to prevent bending due to excessive adhesion. If the separator and the electrode have an excessively high wet adhesive strength, the difference between the dry adhesive strength and wet adhesive strength of the separator to the negative electrode is greater than the difference between the dry adhesive strength and wet adhesive strength of the separator to the positive electrode, which may induce bending. If the adhesive strength between the separator and the electrode is too high, the binder in the separator may hinder the diffusion and wettability of the electrolyte, deteriorating electrolyte impregnation and increasing internal resistance.

[0070] In the present invention, the content of the comonomer in the PVDF-based polymer can be measured by 1H-NMR using Varian 500MHz. For details of the measurement method, refer to Journal of Materials Chemistry, 2012, 22, 341 or AMT-3412-0k. The NMR spectrum can be confirmed using appropriate equipment such as Bruker Avance III HD 700Mhz NMR or Varian 500MHz NMR.

[0071] In the present invention, the acrylic polymer may preferably be a (meth)acrylic acid ester-styrene copolymer or an acrylic-styrene copolymer. Specific examples of such (meth)acrylic acid esters include, for example, methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, i-propyl (meth)acrylate, n-butyl (meth)acrylate, i-butyl (meth)acrylate, n-amyl (meth)acrylate, i-amyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, nonyl (meth)acrylate, and (meth)acrylate. Examples of the acrylate include decyl acrylate, hydroxymethyl (meth)acrylate, hydroxyethyl (meth)acrylate, ethylene glycol (meth)acrylate, ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, allyl (meth)acrylate, and ethylene di(meth)acrylate, and one or more selected from these may be used. Among these, one or more selected from methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate are preferred, and butyl (meth)acrylate is particularly preferred.

[0072] More specifically, the acrylic-styrene copolymer may include an acrylic binder, and the acrylic binder may be a polyacrylate. For example, the binder may be at least one selected from the group consisting of styrene-butadiene rubber, nitrile-butadiene rubber, acrylonitrile-butadiene rubber, acrylonitrile-butadiene-styrene rubber, and acrylate-based polymers, and in particular may be a copolymer containing acrylate.

[0073] According to one example, the acrylic polymer is a (meth)acrylic acid ester-styrene copolymer, and the styrene may be 50 to 80 parts by weight based on 100 parts by weight of the comonomer constituting the acrylic polymer. The styrene has a relatively high crystallinity and Tm (melting temperature) compared to (meth)acrylic acid esters, such as butyl acrylate, and therefore may affect the dry adhesive strength when included in a certain content range during copolymerization. If the styrene is less than 50 parts by weight, the Tg is low and melt deformation of the acrylic polymer occurs during the drying process of the separator, so that the dry adhesive strength may not be as expected. If the styrene is more than 80 parts by weight, the crystallinity is high, and the acrylic polymer is relatively less sticky even if its shape is maintained.

[0074] In one embodiment of the present invention, the acrylic polymer particles may have a glass transition temperature (Tg) of 40°C to 60°C.

[0075] In one embodiment of the present invention, the inorganic particles may have a non-rectangular structure. When inorganic particles satisfying the above structure are used, the separator has an appropriate air permeability without hindering the adhesive force formation of the separator. The inorganic particles may have a D50 of 0.1 μm to 1 μm. The non-rectangular structure may have an aspect ratio of 1 to 10.

[0076] Specifically, in one embodiment of the present invention, the inorganic particles may be Al2O3.

[0077] According to one embodiment, the modulus of the separator measured in the separator feed direction (MD) is 4,000 kgf / cm 2 More than 10,000kgf / cm 2 Less than or equal to 5,000kgf / cm 2 More than 8,000kgf / cm 2 The kinetic friction coefficient of the separator is more than 0.1 and 0.35 or less, 0.15 to 0.33, or 0.2 to 0.3. FIG. 5 is a schematic diagram showing a separator according to the present invention. The direction perpendicular to the short side w of the separator 14, that is, the long side length of the separator 14, corresponds to the supply direction MD of the separator 14. In this case, the separator may have the above-mentioned modulus and kinetic friction coefficient. Such modulus and kinetic friction coefficient not only affect the wet or dry adhesive force to the positive electrode or negative electrode, but also reduce the problem of the occurrence of wrinkles or misalignment defects of the separator during the stacking process of the electrode assembly. The reduction of such problems is further required when the size of the electrode assembly increases, such as in a large-capacity electrode assembly. Therefore, it is possible to provide an electrode assembly with uniform and excellent performance by preventing wrinkles and maintaining alignment in a large-capacity electrode assembly. The length of the short side of the separator may be 500 mm or more, preferably 600 mm or more. The length of the short side of the separator may be the length of the long side of the electrode assembly, that is, the length of the short side of the separator means the length in a direction perpendicular to the feed direction of the separator.

[0078] In the present specification, the length of the short side of the porous substrate is equal to the length of the short side of the separator, and the length of the short side of the separator refers to the side perpendicular to the separator feeding direction (MD; Machine Direction). As described below, the short side can be expressed as width.

[0079] The modulus of the separator may be a value measured in the separator feeding direction (MD; Machine Direction).

[0080] In one embodiment of the present invention, the separator has a modulus of 4,000 kgf / cm measured in the separator feed direction (MD; Machine Direction). 2 ~30,000kgf / cm 2 , preferably 5,000 kgf / cm 2 ~30,000kgf / cm 2 , more preferably 5,500 kgf / cm 2 ~28,000kgf / cm 2 may be also possible.

[0081] In this specification, the modulus of the separator was measured by preparing a separator test piece having a width of 15 mm and a length of 15 cm, and performing a tensile test on the separator test piece using a Universal Testing Machine (UTM). More specifically, the speed condition of the Universal Testing Machine was set to 50 mm / min to perform the test, and the modulus was measured at the load applied when the separator test piece was deformed by 2% in the longitudinal direction. That is, the longitudinal direction here means the MD direction of the separator, and the width means the length of the short side of the separator.

[0082] In one embodiment of the present invention, the separator may have a kinetic friction coefficient of more than 0.1 and not more than 0.35, for example, not less than 0.2 and not more than 0.3.

[0083] In this specification, the kinetic friction coefficient of the separator was measured using a Heidon 14FW friction / wear tester for the separator test piece. The friction / wear tester used a 0.1 mmR diamond pin, and measured the kinetic friction coefficient for the separator under the conditions of a weight of 5 g and 50 mm / min.

[0084] In this way, when the modulus and kinetic friction coefficient of the separator satisfy the above conditions and ranges, an electrode assembly with excellent performance can be manufactured using the separator. Specifically, the occurrence of wrinkles and misalignment defects in the separator during stacking while supplying the separator to the stack table can be prevented. As a result, an electrode assembly with uniform and excellent performance can be manufactured.

[0085] In one embodiment of the present invention, the organic / inorganic composite porous coating layer may have a thickness of 2 μm to 5 μm. When the coating layer satisfies the above thickness range, the separator according to the present invention is more likely to have the desired modulus and kinetic friction coefficient.

[0086] In one embodiment of the present invention, the porous substrate may have a porosity of 20% to 60%, preferably 25% to 55%.

[0087] In one embodiment of the present invention, the porous substrate may have pores with a size of 20 nm to 25 nm.

[0088] In one embodiment of the invention, the compressibility of said porous substrate may be less than 10%, preferably less than 8%.

[0089] In one embodiment of the present invention, the compressibility was calculated by heating and pressing the porous substrate at a temperature of 70° C. and a pressure of 4 MPa for 1 second, and then calculating the change in thickness after heating and pressing, that is, calculated according to the following formula 1.

[0090] [Formula 1] Compressibility (%) = [(porous substrate thickness before heating and pressing - porous substrate thickness after heating and pressing) / porous substrate thickness before heating and pressing] x 100 (%) When the compression ratio range is satisfied, the modulus value according to the present invention can be obtained. The compression ratio is also called thickness deformation ratio.

[0091] <Secondary battery> One embodiment of the present invention provides a secondary battery that satisfies the following formula 1.

[0092] [Formula 1] X<5mm In the above formula 1, X means the maximum distance measured from an imaginary reference line connecting two opposing sides of the upper surface of the secondary battery to the lowest point of the upper surface of the secondary battery in a state where the secondary battery is placed on a flat surface with the concave side of the secondary battery facing up after the activation process of the secondary battery. Here, when the degree of concavity of the opposing surfaces of the secondary battery is equal, the measurement is performed with one of the surfaces facing up.

[0093] Satisfying the formula 1 means that bending does not occur in the secondary battery after activation. That is, after the activation process of the secondary battery, one side of the secondary battery has a partially concave shape as shown in Fig. 4. In this case, as shown in Fig. 4, the secondary battery is placed on a flat surface with the concave side of the secondary battery facing up, and the maximum distance from an imaginary reference line connecting two opposing sides of the upper surface of the secondary battery to the lowest point of the upper surface of the secondary battery is measured.

[0094] Specifically, a flat ruler (hereinafter, ruler a) is placed on two opposing sides of the upper surface of the secondary battery, and a separate flat ruler (hereinafter, ruler b) is used to measure the maximum distance to the lowest point of the upper surface of the secondary battery. In this case, if the maximum distance from one side of ruler a to the lowest point of the upper surface of the secondary battery measured using ruler b is less than 5 mm, it is defined that there is no bending. According to the above definition, (a) of FIG. 4 shows a case where bending has occurred, and (b) of FIG. 4 shows a case where bending has not occurred.

[0095] In one embodiment of the present invention, the electrode assembly may be free of bending after an activation process, which means that the electrode assembly taken out by opening the battery case after the activation process may also be free of bending.

[0096] <Secondary battery manufacturing method> One embodiment of the present invention provides a method for manufacturing a secondary battery, which includes a step of activating a secondary battery, and satisfies the formula 1. Thus, the method for manufacturing a secondary battery of the present invention can provide a secondary battery that is not bent after the activation step.

[0097] A method for manufacturing a secondary battery according to an example includes the steps of: providing an electrode assembly according to the above embodiment in a battery case; sealing the battery case; injecting an electrolyte into the battery case; and The method includes activating the secondary battery.

[0098] In one embodiment of the present invention, the method for manufacturing a secondary battery may further include laminating the positive electrode, the negative electrode, and the separator before the step of providing the electrode assembly in the battery case. For example, the lamination can be performed by heating and pressurizing the secondary battery. The step of heating and pressurizing the secondary battery can be performed under conditions of a temperature of 30° C. to 90° C., a pressure of 2 Mpa to 5 Mpa, and a time of 15 seconds to 30 seconds before the step of providing the electrode assembly in the battery case. The step of heating and pressurizing the secondary battery is performed before the step of activating the secondary battery, and means a step different from the heating and pressurizing process in the process of laminating the electrodes and the separator to manufacture the electrode assembly. The lamination step can be performed without a jig (free jig formation). The lamination step under such conditions can affect the wet or dry adhesive strength between the separator and the positive electrode or the negative electrode. If the lamination conditions are not within the above ranges, it is difficult to obtain the desired dry adhesive strength, and the assembly in the next step is difficult. Also, if the lamination conditions are beyond the above ranges, although the adhesive strength is excellent, it is difficult to control the wetting of the electrolyte, and the adhesive strength of the separator to the positive and negative electrodes becomes unbalanced, which may further worsen bending.

[0099] In one embodiment of the present invention, the step of activating the secondary battery may include degassing after charging once or more, for example, 2 to 3 times, under conditions of 25°C to 60°C, pressure of 0.1 MPa to 0.9 MPa, current of 0.2 C to 0.8 C, for example, 0.3 C to 0.7 C, 0.4 C to 0.6 C or 0.5 C, and state of charge (SOC) of 30% to 60%. The conditions of such an activation step may also affect the wet or dry adhesive strength between the separator and the positive electrode or negative electrode. If the temperature is too high in the activation step, the balance of the adhesive strength between the positive electrode and the negative electrode may be lost, accelerating bending, and if the state of charge (SOC) is less than 30%, a preferable SEI film cannot be formed, and if it exceeds 60%, bending may occur due to volume expansion and contraction of the negative electrode. The activation step may be performed under pressure with a jig to satisfy the above-mentioned pressure conditions. By carrying out activation while applying pressure with a jig, bending can be minimized even without a jig during charge and discharge conditions after the activation stage. However, if pressure is too high, lithium deposition can occur due to binder resistance caused by high adhesion.

[0100] In an embodiment of the present invention, the method for manufacturing a secondary battery may further include a step of manufacturing the electrode assembly prior to the step of providing the electrode assembly in the battery case. The step of manufacturing the electrode assembly may include: a positive electrode supply stage for supplying positive electrodes to the stack table; a negative electrode supplying step of supplying a negative electrode to the stack table; a separator supplying step of supplying a separator to the stack table; stacking a stack including the positive electrode, the separator, and the negative electrode on the stack table; and The method may include a heat pressing step in which the laminate is heated and pressed.

[0101] According to one embodiment, the separator supply step comprises supplying the separator at a pressure of 0.1 kgf / cm 2 The material may be supplied under pressure.

[0102] In one embodiment of the present invention, the heat pressing step includes a lower plate on which the electrode assembly to be heated and pressed is placed and to which heat can be applied, and an upper plate corresponding to the lower plate and to which heat can be applied. The upper plate and the lower plate may be a pair of pressing blocks.

[0103] In one embodiment of the present invention, the stacking step may include the steps of: providing the positive electrode on a stack table; providing the negative electrode on the stack table; and providing the separator on the stack table.

[0104] That is, the stacking step may further include the steps of: supplying the positive electrode onto a stack table; and supplying the negative electrode onto the stack table.

[0105] In one embodiment of the present invention, the step of supplying the separator to the stack table includes the steps of: loosening the separator wound around a separator roll; and applying 0.1 kgf / cm 2 The separator may be pressurized by a separator dancer portion, which will be described later.

[0106] In accordance with an embodiment of the present invention, the method for manufacturing an electrode assembly may further include a step of transferring the stack to a heat press step after the stacking step. In order to transfer the stack in the transferring step, the stack may be gripped by a gripper.

[0107] In one embodiment of the present invention, the gripper can maintain grip on the laminate during the heat pressing step, which can be referred to as a first heat pressing step.

[0108] In one embodiment of the present invention, the gripper can stop gripping the laminate at the heat pressing stage, which is referred to as a second heat pressing stage.

[0109] Furthermore, in one embodiment of the present invention, the heat pressing step may be performed only once by stopping the gripping of the laminate.

[0110] In one embodiment of the present invention, the step of manufacturing a stack in which positive and negative electrodes are alternately arranged between folded separators may use a technique commonly used in the art. For example, the step of stacking positive electrodes on the stack table, covering the positive electrodes with a separator, stacking a negative electrode on the upper surface of the separator, folding the separator to cover the negative electrode, and then stacking a positive electrode on the upper surface of the separator may be repeated. This is called a zigzag stacking method in this embodiment. In this case, the step of the separator moving while covering the positive or negative electrode placed on the separator may be a method in which the stack table moves left and right, a method in which the separator moves left and right, or a method in which the stack table rotates.

[0111] In the zigzag stacking method, a holding mechanism can grip the stack to maintain alignment of the stack as the positive electrodes, negative electrodes, and separators are stacked.

[0112] In this specification, the "holding mechanism" refers to a mechanism that grips the stack placed on the stack table in order to stack positive electrodes or negative electrodes in the zigzag stacking method, and is different from the gripper that grips the stack in the heat press stage.

[0113] In one embodiment of the present invention, the separator may be provided in the form of a separator sheet. That is, the additional separator may be provided in a continuous form. Also, the "upper surface" may refer to the surface opposite to the surface on which the separator or electrode is placed on the stack table.

[0114] In an embodiment of the present invention, the heat pressing step may be performed by applying pressure to the laminate in the lamination axis direction while heating the laminate. The heat pressing step may be performed by a heat press unit described later.

[0115] Furthermore, in one embodiment of the present invention, the heat pressing step may include a step of moving the laminate between a pair of pressure blocks including a press heater; a step of the pair of pressure blocks moving toward each other in the stacking axis direction to apply surface pressure to the laminate; and a step of heating the laminate.

[0116] The pair of pressure blocks may be a lower plate and an upper plate facing the lower plate.

[0117] Furthermore, in one embodiment of the present invention, the heat pressing step may include the steps of: moving the laminate between a pair of pressure blocks; moving the pair of pressure blocks in the lamination axis direction to apply surface pressure to the laminate; and heating the laminate by a separately provided press heater.

[0118] That is, the press heater may be included in the pressurizing block, or may be provided as a separate structure.

[0119] As described above, the method for manufacturing an electrode assembly according to an embodiment of the present invention may further include a step of releasing or loosening the gripper before the heat pressing step. The step of releasing the gripper may include a step of stopping the gripper from pressing the upper surface of the laminate; and a step of moving the gripper away from the laminate.

[0120] In addition, in the heat pressing step, the step of moving the laminate between a pair of pressurizing blocks including a press heater may include a case where only the laminate itself is moved, and a case where the laminate is placed on a stack table and moved together with the stack table. In this case, the objects to be heated and pressed by the pair of pressurizing blocks and the press heater may refer to the laminate and the stack table.

[0121] In one embodiment of the present invention, the heat pressing step may heat and press the laminate for 15 to 30 seconds at a temperature of 30°C to 90°C and a pressure of 2 MPa to 5 MPa. More preferably, the laminate may be heated and pressed for 15 to 30 seconds at a temperature of 60°C to 90°C and a pressure of 2.5 MPa to 4.5 MPa. More preferably, the laminate may be heated and pressed for 15 to 25 seconds at a temperature of 65°C to 85°C and a pressure of 3 MPa to 4 MPa.

[0122] When the above conditions are satisfied, the adhesive strength between the positive electrode and the separator and between the separator and the negative electrode can be improved without damaging the positive electrode, the separator and the negative electrode, thereby improving the performance of the electrode assembly.

[0123] For reference, a semi-finished product state in which a positive electrode, a separator, and a negative electrode are repeatedly stacked can be referred to as a laminate, and a separate component obtained by performing a separator winding process on the semi-finished product can be classified as an electrode assembly.

[0124] Furthermore, one embodiment of the present invention can provide an electrode assembly manufacturing apparatus to which the electrode assembly manufacturing method can be applied.

[0125] Specifically, the manufacturing apparatus for an electrode assembly according to the present invention may include a separator supply unit that supplies a separator to the stack table; a positive electrode supply unit that supplies a positive electrode to the stack table; and a negative electrode supply unit that supplies a negative electrode to the stack table.

[0126] In one embodiment of the present invention, the heat press unit may be composed of a pair of pressure blocks, which move in directions opposite to each other to apply surface pressure to the laminate.

[0127] The heat press unit includes a pair of pressurizing blocks and a press heater for heating the pressurizing blocks. While the press heater heats the pressurizing blocks, the pair of pressurizing blocks move in directions facing each other, so that the laminate placed between the pressurizing blocks can be surface-pressurized.

[0128] In this case, the pair of pressurizing blocks may include press heaters therein.

[0129] In another embodiment of the present invention, the heat press section may be two separate heat press sections, i.e., a first heat press section and a second heat press section.

[0130] Referring to FIG. 9, the first heat press unit may include a pair of first pressure blocks. The pressure surfaces of the pair of first pressure blocks may include grooves having a shape corresponding to the grippers so that the grippers can press the laminate while gripping the laminate. The pressure surfaces other than the grooves may be flat. The second heat press unit may include a pair of second pressure blocks. The pressure surfaces of the pair of second pressure blocks may be flat. That is, when the laminate is placed on the pressure surfaces of the pressure blocks, the second pressure blocks can move relative to each other to heat and press the laminate.

[0131] By dividing the heat press section into two sections as described above, it is possible to prevent the heated laminate from being cooled while being transported, and thus prevent the adhesive strength between the layers inside the laminate from being lost.

[0132] The conditions for heating and pressing the laminate in the heat press section are the same as those in the heat press step described above.

[0133] In addition, the electrode assembly manufacturing apparatus according to the present invention may include a gripper that grips the laminate during a process of transferring the laminate from the stack table to the heat press unit. The gripper may grip and release the laminate in the above-described manner.

[0134] In this specification, the term "unit" refers to an interface that performs a specific function within an electrode assembly manufacturing apparatus.

[0135] In one embodiment of the present invention, the stack table may include a table body on which the stack body is placed and a drive unit that drives the table body. The table body may include a stack table heater that can heat the stack body to a predetermined temperature when the stack body is placed on the table body.

[0136] In one embodiment of the present invention, the positive electrode supply section may include at least one of a positive electrode mounting table, a positive electrode roll, a first cutter, a first conveyor belt, and a positive electrode supply head.

[0137] Furthermore, the positive electrode mounting table may include a positive electrode heater that heats the positive electrode placed on the positive electrode mounting table to a predetermined temperature.

[0138] In one embodiment of the present invention, the negative electrode supply section may include at least one of a negative electrode mounting table, a negative electrode roll, a second cutter, a second conveyor belt, and a negative electrode supply head.

[0139] Furthermore, the negative electrode mounting table may include a negative electrode heater that heats the negative electrode placed on the negative electrode mounting table to a predetermined temperature.

[0140] In one embodiment of the present invention, the positive electrode stacking unit may include a first suction head that vacuum-sucks the positive electrode mounted on the positive electrode mounting table. The positive electrode can be moved from the positive electrode mounting table to the stack table via the positive electrode stacking unit.

[0141] The negative electrode stacking unit may include a second suction head that vacuum-sucks the negative electrodes mounted on the negative electrode mounting table. The negative electrodes can be moved from the negative electrode mounting table to the stack table via the negative electrode stack unit.

[0142] In one embodiment of the present invention, the current collector, active material, conductive material, etc. used in the positive electrode and the negative electrode may be any active material known in the art, and the method for manufacturing the positive electrode and the negative electrode may be any method known in the art, without any limitation.

[0143] Fig. 6 shows a process flow of an electrode assembly manufacturing apparatus according to an embodiment of the present invention in a cross-sectional view, and Fig. 7 shows a process flow of an electrode assembly manufacturing apparatus according to an embodiment of the present invention in a plan view. For convenience, Fig. 6 omits the holding mechanism 170 and the heat press unit 180 shown in Fig. 7, and Fig. 7 omits the separator supply unit 120 shown in Fig. 6.

[0144] 6 to 8, an electrode assembly manufacturing apparatus 100 according to an embodiment of the present invention includes a separator supplying unit 120 that supplies a separator 14 to a stack table 110, a positive electrode supplying unit 130 that supplies a positive electrode 11 to the stack table 110, and a negative electrode supplying unit 140 that supplies a negative electrode 12 to the stack table 110. In this case, the separator 14, the positive electrode 11, and the negative electrode 12 may be heated in the positive electrode supplying unit 130 and the negative electrode supplying unit 140, respectively, and then supplied to the stack table 110.

[0145] In addition, the electrode assembly manufacturing apparatus 100 according to an embodiment of the present invention includes a positive electrode stacking unit 150 for stacking the positive electrodes 11 supplied by the positive electrode supply unit 130 on the stack table 110, and a negative electrode stacking unit 160 for stacking the negative electrodes 12 supplied by the negative electrode supply unit 140 on the stack table 110. At this time, the separators 14 supplied by the separator supply unit 120 are stacked in a zigzag shape while alternately moving back and forth between the left side of the stacking axis and the right side of the stacking axis based on the stacking axis. At this time, the positive electrodes 11 and the negative electrodes 12 are alternately inserted into the spaces (between the separators) generated by folding the separators 14, and as a result, a stack in a form in which the positive electrodes 11, the separators 14, the negative electrodes 12, and the separators 14 are repeatedly stacked is placed on the stack table 110.

[0146] The separator supply section 120 may include a separator heating section 121 and a separator roll 122. The separator heating section 121 is selectively applicable.

[0147] More specifically, the positive electrode supply unit 130 may include a positive electrode mounting table 131, a positive electrode heater (not shown), a positive electrode roll 133, a first cutter 134, a first conveyor belt 135, and a positive electrode supply head 136. The positive electrode heater (not shown) is selectively applicable.

[0148] The negative electrode supply unit 140 may also include a negative electrode mounting table 141, a negative electrode heater (not shown), a negative electrode roll 143, a second cutter 144, a second conveyor belt 145, and a negative electrode supply head 146. The negative electrode heater (not shown) is optional.

[0149] The positive electrode stacking unit 150 stacks the positive electrodes 11 on the stack table 110. At this time, the positive electrode stacking unit 150 may include a first suction head 151, a first head heater (not shown), and a first moving unit 153. In addition, the negative electrode stacking unit 160 stacks the negative electrodes 12 on the stack table 110. The negative electrode stacking unit 160 may include a second suction head 161, a second head heater (not shown), and a second moving unit 163.

[0150] The positive electrode stack unit 150 and the negative electrode stack unit 160 may further include a heater (not shown) for preheating the positive electrode and the negative electrode, if necessary.

[0151] Furthermore, the electrode assembly manufacturing apparatus 100 according to an embodiment of the present invention may further include a holding mechanism 170 that fixes the positive electrode 11 and the negative electrode 12 when they are stacked on the stack table 110. Furthermore, the electrode assembly manufacturing apparatus 100 according to an embodiment of the present invention includes a heat press unit 180 that applies heat and pressure to the stack placed on the stack table 110 to bond the positive electrode 11, the separator 14, and the negative electrode 12 together.

[0152] In addition, the electrode assembly manufacturing apparatus 100 according to an embodiment of the present invention further includes an induction heating unit (not shown) that inductively heats the laminate and transfers heat to the electrodes in the laminate. Also, the apparatus may further include a control unit (not shown) that controls whether the induction heating unit (not shown) is operated. As a result, the electrode assembly 10 as shown in FIG. 7 can be finally manufactured.

[0153] FIG. 8 is a cross-sectional view illustrating an example of an electrode assembly manufactured by an apparatus for manufacturing an electrode assembly and a method for manufacturing an electrode assembly according to an embodiment of the present invention.

[0154] Referring to FIG. 8, the electrode assembly 10 may have a configuration in which separators are stacked while being folded in a zigzag shape, and positive electrodes or negative electrodes are inserted into spaces between the separators in an alternating manner.

[0155] In this case, the electrode assembly 10 may be provided in a form in which the outermost corners of the laminate are wrapped with the separators 14. However, the configuration of the electrode assembly 10 is not limited to the example shown in FIG.

[0156] FIG. 9 shows the configuration of a heat press 50, and in particular shows a case where the heat press section 50 includes a first heat press section 50 and a second heat press section 60. As shown in FIG.

[0157] FIG. 9( a ) is a perspective view showing the first heat press unit 50 , and FIG. 9( b ) is a perspective view showing the second heat press unit 60 .

[0158] 9(a), the first heat press unit 50 can apply heat and pressure to the laminate S while it is fixed by the gripper 51. The first heat press unit 50 may be composed of a pair of first pressure blocks 50a, 50b. The pair of first pressure blocks 50a, 50b have all of their pressure surfaces flat except for a groove having a shape corresponding to the fixing portion 51b of the gripper 51.

[0159] The gripper 51 may include a main body 51a that corresponds to the length x and height y of the stack S or is wider than the length x and height y of the stack S, and a fixing portion 51b that protrudes from the main body 51a and grips the stack S. Here, the length x of the stack S may refer to the portion where the distance from one end to the other end of the stack S is the longest, the height y may refer to the distance in the stacking direction of the stack S, and the width z may refer to the distance across the top surface of the stack S.

[0160] The fixing portion 51b is capable of adjusting its position along the height direction of the main body 51a, and the fixing portion 51b is capable of contacting the upper and lower surfaces of the stack S to fix the stack S.

[0161] Thereafter, the pair of first pressurizing blocks 50a, 50b move in directions opposite to each other to heat and pressurize the laminate S. By the heating and pressing, the electrodes and separators inside the electrode assembly are stably bonded to each other.

[0162] The first heat press unit 60 may be a component that complements the cooling of the induction-heated electrode assembly while it is moving, and may be provided selectively. That is, it may be omitted in some cases.

[0163] 9(b), the second heat press unit 60 can finally heat and pressurize the laminate S that has been primarily heated and pressed by the first heat press unit 50. The second heat press unit 60 includes a pair of second pressurizing blocks 60a, 60b, which are moved in directions opposite to each other to apply surface pressure to the laminate S. In addition, the pair of second pressurizing blocks 60a, 60b included in the second heat press unit 60 may all be provided with flat pressure surfaces that come into contact with and pressurize the laminate S. EXAMPLES

[0164] Although the embodiments of the present invention have been described in detail above, the scope of the invention is not limited thereto, and it will be obvious to those having ordinary skill in the art that various modifications and variations are possible without departing from the technical idea of ​​the invention described in the claims.

[0165] The physical properties and performance of the separators, electrode assemblies and secondary batteries prepared in the following examples and comparative examples were measured as follows.

[0166] <Experimental Example 1>-Dry Adhesion Measurement The dry adhesive strength of the electrode assembly to the negative electrode and the dry adhesive strength to the positive electrode were measured by cutting a part of the electrode assembly to a size of 20 mm x 70 mm before immersing the electrode assembly in the electrolyte, preparing a test piece in which the positive electrode separator and the negative electrode were laminated, and then peeling the separator of the test piece at a speed of 100 mm / min using a tensile tester (UTM equipment) in a 90° peeling mode from one side of the separator. The results are shown in Tables 1 to 3 below.

[0167] <Experimental Example 2>-Wet Adhesion Strength Measurement After the activation process was completed, the electrode assembly of the secondary battery was removed from the pouch exterior material, and a part of the electrode assembly (impregnated with electrolyte) was cut into a size of 20 mm x 70 mm to prepare a test specimen in the form of a laminated positive electrode separator and a negative electrode. After preparing the test specimen, the separator of the test specimen was peeled from one side of the separator in a 90° peel mode at a speed of 100 mm / min using a tensile tester (UTM equipment) to measure the wet adhesive strength of each electrode assembly. The results are shown in Tables 1 to 3 below. That is, the method of measuring the dry adhesive strength and the wet adhesive strength was the same as described above, except for whether the electrode assembly was impregnated with electrolyte or not.

[0168] <Experimental Example 3> - Measurement of separator surface components After the activation process, the electrode assembly of the secondary battery was removed from the pouch exterior material, and the separator was immersed in dimethyl carbonate solvent for 30 minutes to remove electrolyte additives and metal salt components remaining on the separator surface. The separator was then dried at room temperature for 24 hours, and the surface components were measured and observed according to the above-mentioned method. The results are shown in Tables 1 to 3 below.

[0169] <Experimental Example 4> - Bending level measurement The secondary batteries including the electrode assemblies after the activation process were placed on a flat surface with the concave side facing up. Then, a flat ruler (hereinafter, ruler A) was placed on the secondary battery so as to correspond to an imaginary reference line connecting two opposing sides of the upper surface of the secondary battery, and a separate flat ruler (hereinafter, ruler B) was used to measure the maximum distance to the lowest point of the upper surface of the secondary battery. The results are shown in Tables 1 to 3 below. For reference, it was defined that there was no bending when the measured distance was less than a maximum of 5 mm.

[0170] <Experimental Example 5>-Separator resistance after activation After the activation process was completed, the electrode assembly of the secondary battery was removed from the pouch exterior material, and the separator was immersed in dimethyl carbonate solvent for 30 minutes to remove electrolyte additives and metal salt components remaining on the separator surface. The separator was then dried at room temperature for 24 hours to check its resistance characteristics.

[0171] Specifically, the separator was cut and stacked in a Hoshen 2032 coin cell, and the resistance value when impregnated with the electrolyte was measured by EIS (Electrochemical Impedance Spectroscopy) at 25°C using an AC method with a 1M LiPF6-ethylene carbonate / ethyl methyl carbonate (weight ratio 3:7) electrolyte, and the results are shown in Tables 1 to 3 below.

[0172] <Experimental Example 6> - Measurement of separator modulus and kinetic friction coefficient The modulus of the separator was measured. Specifically, a separator test piece having a width of 15 mm and a length of 15 cm in the MD direction of the separator was prepared, and a tensile test was performed on the separator test piece using a Universal Testing Machine (UTM). More specifically, the speed condition of the Universal Testing Machine was set to a speed of 50 mm / min to proceed the test, and the modulus was measured at the load applied when the separator test piece was deformed by 2% in the longitudinal direction.

[0173] In addition, a separator test piece with a width of 5 cm and a length of 5 cm in the MD direction of the separator was prepared, and the separator test piece was measured using a Heidon 14FW friction / wear tester. At this time, the friction / wear tester used a 0.1 mmR diamond pin, and the kinetic friction coefficient for the separator was measured under the conditions of a weight of 5 g and 50 mm / min.

[0174] <Experimental Example 7> - Evaluation of shrinkage rate The separator was evaluated by measuring its thermal shrinkage. Specifically, when the thermal shrinkage of the separator was measured at 130° C. and a thermal shrinkage of more than 5% was observed in either the MD or TD direction, the separator was determined to be defective and insufficient.

[0175] <Experimental Example 8> - Evaluation of assembly process The electrode assembly was evaluated for the presence or absence of separator wrinkles and the degree of distortion of the lamination (wandering). Specifically, the presence or absence of separator wrinkles in the electrode assembly was evaluated by disassembling the electrode assembly and visually inspecting the internal separator for wrinkles, and if even one wrinkle was observed, it was judged to be defective. In addition, the electrode assembly was evaluated for meandering by visually inspecting the edge of the separator located in the electrode tab portion of the electrode assembly, and if the edge of the separator was distorted by 1 mm or more, it was judged to be defective.

[0176] Example 1 <Manufacturing of electrode assembly> To manufacture the negative electrode, a mixture of artificial graphite as a carbon-based active material, a binder polymer (SBR (styrene-butadiene rubber) and CMC (carboxymethyl cellulose)), and carbon black as a conductive material in a weight ratio of 95.5:3:1.5 was mixed with water as a dispersion medium in a weight ratio of 1:2 to prepare a slurry for the first active material layer.

[0177] As the silicon-based active material, silicon oxide with a Coulombic efficiency of 80% or more when charged and discharged at 0.1 C was prepared, and a slurry for the second active material layer was prepared that was the same as that for the first active material layer, except that the carbon-based active material (artificial graphite) and the silicon-based active material were mixed in a weight ratio of 9:1, and carbon nanotubes were added as a conductive material. That is, the weight ratio of the active material, binder polymer, carbon black, and carbon nanotubes (CNT) was 95.5:3:1.0:0.5, and the weight ratio of the carbon-based active material to the silicon-based active material in the active material was 9:1.

[0178] The specific surface area of ​​the carbon nanotube (CNT) is 550m2 The carbon nanotubes (CNTs) were multi-walled carbon nanotubes.

[0179] Using a double slot die, the slurry for the first active material layer was coated on one side of a copper (Cu) thin film, which was a negative electrode current collector having a thickness of 10 μm, and then the slurry for the second active material layer was coated on the slurry for the first active material layer and dried under vacuum at 130° C. for 1 hour to form a first active material layer and a second active material layer.

[0180] The first and second active material layers thus formed were simultaneously rolled by roll pressing to prepare a negative electrode. At this time, the thickness ratio of the first and second active material layers was 1:1. The loading amount of the first and second negative active material layers was 512 mg / 25 cm based on the dry weight. 2 (Total thickness of dry negative electrode: 292 μm).

[0181] Next, to manufacture the positive electrode, Li(Ni 0.3 Mn 0.5 Co 0.2 A positive electrode active material slurry was prepared by adding 100% ethylenediaminetetraacetate (100% ethylenediaminetetraacetate) (NCM-352), carbon black as a conductive material, and polyvinylidene fluoride (PVdF) as a binder in a weight ratio of 96:2:2 to a solvent, N-methylpyrrolidone (NMP). The slurry was coated on one side of an aluminum current collector having a thickness of 15 μm, and dried and rolled under the same conditions as the negative electrode to prepare a positive electrode. In this case, the loading amount based on the dry weight of the positive electrode active material layer was 988 mg / cm. 2 (Total thickness of the positive electrode on a dry basis: 242 μm).

[0182] Finally, a polyethylene film (PE, thickness 9 μm) was prepared as a porous substrate to manufacture a separator. The porous substrate was stretched 8 times in the MD direction at 100°C and 8 times in the TD direction at 125°C. The porous substrate was heated and pressed at a temperature of 70°C and a pressure of 4 MPa for 1 second, and the compression ratio calculated by calculating the thickness change after heating and pressing was 5%.

[0183] Then, the first binder and the second binder were added as particulate binders to distilled water at room temperature so as to satisfy a weight ratio of 60:40. Then, a dispersant was added to the distilled water together with inorganic particles (weight ratio of the first and second binders to the inorganic particles = 20:80) in a ratio of 4 times the total weight of the first binder and the second binder. In this case, the first binder was a copolymer of styrene and butyl acrylate, and the weight ratio of the two monomers (styrene and butyl acrylate) was adjusted to 70: / 30 to have a glass transition temperature (Tg) of 45°C, and the second binder was a PVDF-HFP binder with a content of repeating units derived from HFP of 5 wt%.

[0184] Moreover, Al2O3 was used as the inorganic particles. The inorganic particles had an aspect ratio of 1 to 10 and a D50 of 0.5 μm.

[0185] Then, 0.7 μm zirconia beads were added to the distilled water in the same amount as the inorganic particles, and the mixture was bead-milled for 2 hours using a paint shaker to prepare an inorganic dispersion.

[0186] Then, a surfactant was further added to the inorganic dispersion, and the inorganic dispersion was stirred at 10 rpm for 10 minutes to prepare a slurry in which the binder and inorganic particles were dispersed.

[0187] Then, the slurry was coated on both sides of the polyethylene film (PE, thickness 9 μm) using a doctor blade and dried using a hot air blower to form a porous coating layer with a thickness of 2.5 μm for each coating, thereby preparing a separator of Example 1 with a total thickness of 14 μm. The modulus of the produced separator was 6,000 (kgf / cm 2 ) and the kinetic friction coefficient was 0.25.

[0188] The prepared positive electrode, negative electrode, and separator were fed to a stack table, and the separator was folded to stack the positive electrode, negative electrode, and separator. Specifically, the positive electrode and negative electrode were alternately arranged between the folded separators on the stack table to prepare a stack using 39 electrodes. Then, the stack was heated and pressurized at a temperature of 60° C. and a pressure of 3 MPa for 15 seconds (time condition) to prepare the electrode assembly of Example 1.

[0189] <Secondary battery manufacturing> The electrode assembly of Example 1 was placed in a pouch exterior material (battery case) of CPP / aluminum / nylon laminate sheet, and an ethyl methyl carbonate electrolyte solution containing LiPF6 was injected. The pouch exterior material was then heat-sealed to complete the assembly of the secondary battery.

[0190] Thereafter, the secondary battery was subjected to an activation process in which the secondary battery was charged at 0.5 C up to SOC 50% under temperature conditions of 50° C. and pressure conditions of 0.5 MPa.

[0191] Example 2 The separator was produced in the same manner as in Example 1, except that the first binder and the second binder were added as particulate binders in a weight ratio of 50:50.

[0192] Comparative Example 1 The separator was produced in the same manner as in Example 1, except that the first binder and the second binder were added as particulate binders in a weight ratio of 15:85.

[0193] Comparative Example 2 The separator was produced in the same manner as in Example 1, except that the first binder and the second binder were added as particulate binders in a weight ratio of 70:30.

[0194] Comparative Example 3 The separator was prepared in the same manner as in Example 2, except that the first binder, a copolymer of styrene and butyl acrylate, was used in which the weight ratio of the two monomers (styrene and butyl acrylate) was adjusted to 25:75.

[0195] Comparative Example 4 The separator was prepared in the same manner as in Example 2, except that the first binder, a copolymer of styrene and butyl acrylate, was used in which the weight ratio of the two monomers (styrene and butyl acrylate) was adjusted to 85:10.

[0196] Comparative Example 5 The separator was prepared in the same manner as in Example 2, except that a PVDF-HFP binder having a content of repeating units derived from HFP of 1.5 wt % was used as the second binder.

[0197] Example 3 The separator was prepared in the same manner as in Example 2, except that a PVDF-HFP binder having a repeating unit content of 20 wt % derived from HFP was used as the second binder.

[0198] Comparative Example 6 The separator was manufactured in the same manner as in Example 2, except that inorganic particles having an aspect ratio of 11 were used.

[0199] Comparative Example 7 The same procedure as in Example 2 was carried out, except that the laminate of the positive electrode, the negative electrode and the separator was heated and pressed at a temperature of 20° C. and a pressure of 1 MPa instead of at a temperature of 60° C. and a pressure of 3 MPa.

[0200] Comparative Example 8 The same procedure as in Example 2 was carried out, except that the laminate of the positive electrode, the negative electrode and the separator was heated and pressed at a temperature of 80° C. and a pressure of 6 MPa instead of at a temperature of 60° C. and a pressure of 3 MPa.

[0201] Comparative Example 9 The activation process of the secondary battery was carried out under a charged state (SOC 25%) and a pressure of 0.3 kgf / cm 2 The same procedure as in Example 2 was repeated, except that the pressure was adjusted to 1000 MPa.

[0202] Comparative Example 10 The activation process of the secondary battery was carried out under a charged state (SOC 80%) and a charging voltage of 10 kgf / cm 2 The same procedure as in Example 2 was repeated, except that the pressure was adjusted to 1000 MPa.

[0203] Comparative Example 11 When manufacturing the separator, the porous substrate is stretched 6 times in the MD direction at 100℃ and 5.5 times in the TD direction at 125℃. The modulus of the separator is 2,000 (kgf / cm 2 The procedure was carried out in the same manner as in Example 1, except that

[0204] Comparative Example 12 When manufacturing the separator, the porous substrate is stretched 11 times in the MD direction at 100°C and 10 times in the TD direction at 125°C. The modulus of the separator is 10,000 (kgf / cm 2 The procedure was carried out in the same manner as in Example 1, except that

[0205] Comparative Example 13 The separator was prepared in the same manner as in Example 1, except that the weight ratio of the first and second binders to the inorganic particles in the slurry was 10:90, and the kinetic friction coefficient of the prepared separator was 0.1.

[0206] Comparative Example 14 The separator was prepared in the same manner as in Example 1, except that the weight ratio of the first and second binders to the inorganic particles in the slurry was 60:40, and the kinetic friction coefficient of the prepared separator was 0.4.

[0207] [Table 1]

[0208] [Table 2]

[0209] [Table 3] In Tables 1 to 3, the positive electrode adhesive strength means the adhesive strength of the separator to the positive electrode, and the negative electrode adhesive strength means the adhesive strength of the separator to the negative electrode.

[0210] In Examples 1 and 2, it was confirmed that the electrode assemblies of Examples 1 and 2 did not cause bending because the separator had appropriate wet adhesive strength and dry adhesive strength to the negative electrode and positive electrode.

[0211] In Comparative Examples 1, 3, and 4, the dry adhesive strength of the separator to the negative or positive electrode was too low to proceed with the process after the electrode assembly was manufactured, and therefore the wet adhesive strength of the separator could not be measured. In Comparative Example 1, an excessive amount of fluoropolymer was used in the separator coating layer, and in Comparative Examples 3 and 4, the content of the comonomer of the acrylic polymer in the separator coating layer was changed. In Comparative Example 3, the Tg of the acrylic copolymer was low and melted during the process, and in Comparative Example 4, the Tg of the acrylic copolymer was too high and the dry adhesive strength to the negative electrode was too low, reducing the assembly processability and making it impossible to proceed with the process.

[0212] In Comparative Examples 11 to 14, as described as the results of Experimental Examples 7 and 8, it was impossible to prepare an electrode assembly, and the wet adhesive strength after preparation of the electrode assembly could not be measured. In Comparative Example 11, wrinkles occurred during the zigzag stacking process due to the low elastic modulus of the separator, and in Comparative Example 12, the shrinkage rate of the separator was 50% or more, and meandering failure occurred. In Comparative Example 13, slippery occurred between the separator and the electrode due to the use of a separator with a too small kinetic friction coefficient, and in Comparative Example 14, meandering failure occurred during the separator running due to the friction during the process being too strong due to the use of a separator with a too large kinetic friction coefficient.

[0213] In Comparative Examples 2, 5, 7 and 9, the wet adhesive strength of the separator to the negative electrode or positive electrode was too low, causing an overhang in the laminate, and a problem occurred in which the edges drooped when the cell was lifted.

[0214] When the separator slurry dries, the binder with a low specific gravity must migrate to the surface, and the binder is likely to migrate if the inorganic particles have a uniform shape. However, in Comparative Example 6, the inorganic particles with a large aspect ratio are randomly distributed, so the binder is less likely to migrate to the surface due to the interference of the particles when the slurry dries (binder migration is reduced), and the dry adhesive strength of the separator to the positive electrode and the wet adhesive strength of the separator to the negative electrode were very low.

[0215] In Comparative Examples 8 and 10, the wet adhesion of the separator to the negative electrode was excessively high, and a high bending level was observed.

[0216] Therefore, the electrode assembly of the present application does not undergo bending, and thus the electrodes can be aligned and fixed without shifting from their original positions, and the energy density can be improved, thereby demonstrating excellent performance of the electrode assembly and the secondary battery including the same.

[0217] As shown in Fig. 10, it was confirmed that the electrode assembly of Example 1 did not have wrinkles in the separator, whereas the electrode assembly of Comparative Example 14 had wrinkles in the separator, as shown in Fig. 11. In Fig. 11, a horizontal line was observed in the middle portion, and this line was a wrinkle.

[0218] In addition, as shown in Fig. 12, it was confirmed that the separator ends of the electrode assembly of Example 1 were well aligned (the separator ends were not misaligned by 1 mm or more). On the other hand, it was confirmed that the separator ends of the electrode assembly of Comparative Example 11 were not well aligned, being misaligned by 1 mm or more, as shown in Fig. 13. It is considered that this was caused by meandering of the separators supplied during the manufacturing process of the electrode assembly of Comparative Example 11. [Explanation of symbols]

[0219] 1 Porous substrate 2. Organic / inorganic composite porous coating layer 3 Inorganic particles 4. Fluorine-based polymers 5. Acrylic polymers 10 Electrode assembly 11 Positive electrode 12 Negative electrode 14 Separator 51 Gripper 51a Main unit 51b Fixed part 100 Electrode assembly manufacturing apparatus 110 Stack Table 120 Separator supply section 121 Separator Heater 122 Separator roll 130 Positive electrode supply unit 131 Positive electrode mounting table 133 Positive electrode roll 134 First Cutter 135 First Conveyor Belt 136 Positive electrode supply head 140 Negative electrode supply unit 141 Negative electrode mounting table 143 Negative electrode roll 144 Second Cutter 145 Second Conveyor Belt 146 Negative electrode supply head 150 Positive electrode stack section 151 First Suction Head 153 First Mobile Unit 160 Negative electrode stack section 161 Second Suction Head 163 Second Mobile Section 170 Holding mechanism 171 First holding mechanism 172 Second holding mechanism 180 Press Department 181 (50a, 50b) first pressure block 182 (60a, 60b) second pressure block S laminate

Claims

1. A battery comprising: a positive electrode; a negative electrode; and a separator provided between the positive electrode and the negative electrode; The electrode assembly, wherein the separator has a wet adhesive strength to the negative electrode of 1.5 gf / 20 mm or more and 15 gf / 20 mm or less.

2. The electrode assembly of claim 1 , wherein the separator has a dry adhesive strength to the negative electrode of 8 gf / 20 mm or more and 25 gf / 20 mm or less.

3. The electrode assembly according to claim 1 , wherein the separator has a wet adhesive strength to the negative electrode of 4 gf / 20 mm or more and 6 gf / 20 mm or less.

4. 2. The electrode assembly according to claim 1, wherein the separator contains 0.1 to 8 parts by weight of fluorine (F) based on 100 parts by weight of the separator surface component.

5. The electrode assembly of claim 1 , wherein the wet adhesive strength of the separator to the negative electrode is at least one time greater than the wet adhesive strength of the separator to the positive electrode.

6. The electrode assembly of claim 1 , wherein the wet adhesive strength of the separator to the negative electrode is 1 to 1.4 times the wet adhesive strength of the separator to the positive electrode.

7. The electrode assembly of claim 1 , wherein the negative electrode comprises a silicon-based active material.

8. 2. The electrode assembly of claim 1, wherein the overall length is between 400 mm and 600 mm, and the overall width is between 50 mm and 150 mm.

9. The separator is The present invention includes a porous substrate and an organic / inorganic composite porous coating layer provided on at least one of one surface and the other surface of the porous substrate, The organic / inorganic composite porous coating layer includes a particulate binder resin and inorganic particles, The particulate binder resin includes an acrylic polymer and a fluorine-based polymer, 2. The electrode assembly according to claim 1, wherein a weight ratio of the acrylic polymer to the fluoropolymer is in the range of 20:80 to 60:

40.

10. The modulus of the separator measured in the separator feed direction (MD; Machine Direction) is 4,000 kgf / cm 2 Above, 10,000kgf / cm 2 10. The electrode assembly of claim 9, wherein the separator has a kinetic friction coefficient of more than 0.1 and not more than 0.

35.

11. The electrode assembly of claim 9, wherein the acrylic polymer has a glass transition temperature (Tg) of 40°C to 60°C.

12. the acrylic polymer is a (meth)acrylic acid ester-styrene copolymer, 10. The electrode assembly of claim 9, wherein the styrene is contained in an amount of 50 to 80 parts by weight based on 100 parts by weight of the comonomer constituting the acrylic polymer.

13. The fluoropolymer is a copolymer of vinylidene fluoride and hexafluoropropylene (HFP) (PVdF-HFP), 10. The electrode assembly of claim 9, wherein the hexafluoropropylene is 3 to 18 parts by weight based on 100 parts by weight of the comonomer constituting the copolymer (PVdF-HFP).

14. The electrode assembly of claim 9 , wherein the inorganic particles are non-rectangular in structure.

15. The electrode assembly according to claim 1 , wherein the separators are stacked by folding in a zigzag pattern.

16. A sealed battery case; The electrode assembly according to any one of claims 1 to 15 is included inside the battery case; an electrolyte contained inside the battery case; Including, A secondary battery that satisfies the following formula 1: [Formula 1] X<5mm In the above formula 1, X means the maximum distance measured from an imaginary reference line connecting two opposing sides of the upper surface of the secondary battery to the lowest point of the upper surface of the secondary battery in a state where the secondary battery is placed on a flat surface with the concave side of the secondary battery facing up after the activation process of the secondary battery.

17. Providing an electrode assembly according to any one of claims 1 to 15 in a battery case; sealing the battery case; injecting an electrolyte into the battery case; activating the secondary battery Including, A method for producing a secondary battery, comprising: [Formula 1] X<5mm In the above formula 1, X means the maximum distance measured from an imaginary reference line connecting two opposing sides of the upper surface of the secondary battery to the lowest point of the upper surface of the secondary battery in a state where the secondary battery is placed on a flat surface with the concave side of the secondary battery facing up after the activation process of the secondary battery.

18. 18. The method of claim 17, further comprising laminating the positive electrode, the negative electrode, and the separator under conditions of a temperature of 30° C. to 90° C., a pressure of 2 MPa to 5 MPa, and a time of 15 seconds to 30 seconds, prior to the step of providing the electrode assembly in the battery case.

19. 20. The method of claim 17, wherein the activating the secondary battery comprises charging the secondary battery at least once under conditions of a temperature of 25° C. to 60° C., a pressure of 0.1 MPa to 0.9 MPa, a current of 0.2 C to 0.8 C, and a state of charge (SOC) of 30% to 60%, and then degassing the secondary battery.

Citation Information

Patent Citations

  • Separator for electrochemical device including adhesive layer and electrode assembly including the separator

    JP2019503577A

  • Slurry composition for nonaqueous secondary battery adhesive layers, production method and use

    WO2018180811A1

  • Nonaqueous electrolyte secondary battery

    WO2018207530A1

  • Secondary battery and production method for same

    WO2021131877A1

  • A stepwise electrode assembly, and battery cell, battery pack and device comprising the same

    KR1020130132230A

Cited By

  • Preheating device

    JP7901228B1